The Effect of Irradiation to Sensoric Characteristic, Physic and Microbe in Sie Balu, Acehnese Dried Meat - Wiqayatun Khazanah; Nurliana Nurliana; Rini Safitri (The Faculty of Veterinary Medicine of Syiah Kuala University, 2017)
One of the Acehnese traditional food preserved by the addition of salt, acid and dried was sie balu. The preservation method may lead to changes in the structure and nutritional content. Sie balu with the addition of vinegar, garlic and ginger can reduce the value of water activity (aW), pH and bacterial counts. This condition affects the physical properties and sensory of sie balu. Irradiation can control pathogenic microorganisms in meat without affecting the physical condition. Low-dose irradiation is able to maintain the desired sensory attributes nutritious food products. This study aims to determine the characteristics of the sensory and physic sie baluthat irradiated with increasing doses and the shelf life of 3-6 weeks. Sie balu was made of 10 kg fresh beef, dried in the sun to dry, vacuum and irradiated at doses of 5, 7 and 9 kGy. Sensory test conducted by taste sie balu by trained panelists and fill out the hedonicform. The physical properties based on pH and aW. The microbe total calculated used Total Plate Count.The results showed that the irradiation dose significantly (P 0.05) affected on microbe total, aroma, color, texture and taste of sie balu. Storage time does not affect the sensory properties. Irradiation dose and storage time significantly (P 0.05) on pH and aWsiebalu. The study concluded that irradiation can improve the physical properties, sensory and microorganisme reductionof sie balu.